Psychological Interpretation of Drawings by Color Analysis for Mental Therapy - Kato, Chieko; Kimoto, Tadahiko (European Journal of Applied Sciences, 2015)
In order to provide psychotherapists with an objective criterion for evaluating client's mental states, this paper proposes a method for analyzing a drawing that a client makes in drawing therapy for four psychological primary colors. The method consists of two steps: an image segmentation step and a color analysis step. In the first step, those areas which seem what the client intended to depict are extracted from the entire digitized image. The effective resolution in the extraction is made variable with the values of parameters in mathematically morphological processing. In the second step, the pixels of the extracted areas are classified into four categories, corresponding to the psychological primary colors, as determined by the dominant component of a pixel color. A case study of employing the color analyses in drawing therapy was carried out with a series of drawings which were obtained in an actual clinical therapy. A comparison of the objective results of the analysis and subjective evaluations obtained in the process of cognitive behavioral therapy has demonstrated that the analyses are useful to describe a variation in a client's mental state in terms of psychological properties of colors. In conclusion, the color analysis method in drawing therapy works in cooperation with cognitive behavioral therapy.